Workplace Ostracism Seen through the Lens of Power - Fiset, John; Al Hajj, Raghid; Vongas, John G. (Frontiers in Psychology, 2017)
Drawing on approach/inhibition theory of power, we investigated two factors that influence the manner by which victims react to workplace ostracism: the hierarchical status of the ostracizer and the level of an ostracizee’s external social support including family, friends, and significant others. Across an experimental vignette study (Study 1) and a field study (Study 2), we found support for a three-way interaction with felt ostracism, ostracizee external social support, and ostracizer status influencing victims’ organizational citizenship behavior and deviance directed toward other individuals. In addition, felt ostracism and ostracizee external social support interacted to predict turnover intentions. Overall, victims who were ostracized by a legitimate higher-status authority (e.g., manager) and whose external social support network was limited experienced the most negative outcomes across both studies. Our findings suggest that contextual factors both inside and outside the organization jointly impact the way in which individuals react to perceived workplace ostracism. Implications and future research directions are discussed.